STAKEHOLDERS COLLABORATION TOWARDS SUSTAINABLE FOOD SECURITY: AN AGENT-BASED SIMULATION - Utomo Sarjono Putro; Valid Hasyimi; Santi Novani; Agung Hendriadi (Jurnal Bisnis Manajemen, 2023)
Food security is categorized as a multi-dimensional issue; most policy issues are so complex and strongly rely on the stakeholders’ interaction. The problem-solving of Indonesia's food security will likely happen if the stakeholders agree to collaborate in planning and implementation. Though Indonesia has recorded a positive increase in the Food Security and Vulnerability Atlas score, some issues remain. For example, Indonesia is still importing rice during the harvesting season. This policy is seen as a lack of synergy between governments that puts food producers in a disadvantaged position. Therefore, this research aims to develop a model to analyze collaboration among stakeholders and then to suggest recommendations to promote collaboration among stakeholders in food security problems. By employing agent-based simulation software named SOARS (Spot Oriented Agent Role Simulator), this research attempts to investigate whether collaboration between stakeholders will happen or not, thus identifying the significant attribute. The simulation shows that all agents are willing to collaborate. Also, we find that vision alignment is the easiest attribute to achieve the minimum score to collaborate. On the other hand, knowledge and resource sharing are the most difficult one, which represents reality. This paper is concluded with recommendations to pursue collaboration in food security